Understanding Of Sumbang Duo Baleh In Increasing Positive Behavior From Early Age (Case Study At Istiqamah Early Childhood Education At Agam Regency) - Juliana Juliana; Ismaniar Ismaniar (Universitas Negeri Padang, 2022)
This research is motivated by the phenomenon of the uniqueness of character education learning from the understanding of the sumbang duo baleh's at PAUD Terpadu Inclusion Istiqamah Islamic School Surau Kamba, Ampek Angkek District, Agam Regency. This study aims to determine the methods, media and evaluation of the implementation of character education from the understanding of the sumbang duo baleh in PAUD Istiqamah. This type of research is qualitative with a case study method that uses data collection techniques by means of observation, interviews, and documentation, then analyzed using triangulation techniques. The results of this study are (1) ways of habituation, strengthening and demonstration in the implementation of character education learning from the understanding of the sumbang duo baleh in PAUD Istiqamah, (2) the media used by the educators themselves as role models, pictures and videos, (3) evaluations carried out with authentic assessments and peers in the implementation of character education learning from the understanding of the sumbang duo baleh. The implementation of character education learning from this sumbang duo baleh's understanding is to be able to increase children's positive behavior from an early age.Keywords: Implementation, Learning, Character Education, Sumbang Duo Baleh